Robustness of multi-storey car parks under localised fire—Towards practical design recommendations - Fang, C.; Izzuddin, B.A.; Elghazouli, A.Y.; Nethercot, D.A. (Journal of constructional steel research, 2013)
This paper investigates the influence of different structural design schemes on the progressive collapse resistance of a fire damaged eight-storey reference steel-composite car park via parametric studies. The reliability of the modelling strategy is first validated through comparisons with the results of localised fire tests on sub-frames undertaken as part of the ROBUSTFIRE project. From the confidence gained from the validation study, two fire scenarios, namely, fire at the ground floor and fire at the top floor, are considered for the subsequent parametric study. System failure criteria are proposed to indicate the ‘Robustness Limit State’, and Capacity–Demand Ratios are employed as a comparative index to evaluate the effectiveness of different design schemes. It is found that fire protection coating can be unexpectedly ineffective and in some cases may even cause adverse effects on structural robustness under localised fire, while improving the joint ductility and slab resistance can be more effective. In addition, certain combinations of two or more enhancements schemes can be very beneficial. The findings are used as the basis for making a series of recommendations for use at the preliminary design stage for steel-composite car parks subject to localised fire. •Parametric studies are performed on a multi-storey car park subject to localised fire.•Detailed structural modelling strategy is presented.•Failure criteria based on joint ductility are proposed.•Key factors affecting the robustness are identified.•Design recommendations for improving structural robustness are proposed.